THE EFFECT OF WORK MOTIVATION, COMPETENCY, AND WORK CULTURE ON EMPLOYEE PERFORMANCE AND THE IMPACT ON ORGANIZATIONAL PERFORMANCE AT THE DIRECTORATE GENERAL OF AGRICULTURAL INFRASTRUCTURE AND FACILITIES - Sugiyono, Edi; Fakhri, Fitri Yanti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to determine the effect of work motivation, competence and work culture on employee performance and their impact on organizational performance at the Directorate General of Agricultural Infrastructure and Facilities. Data collection was carried out through filling out questionnaires by PSP Ministry of Agriculture employees from various work backgrounds. The analytical method used is quantitative with the Structural Equation Model (SEM) Path Path analysis approach. In analyzing the research data using descriptive statistical analysis framework and inferential statistics. The research population is the employees of the Directorate General of Agricultural Infrastructure and Facilities 300 people, while the sample is 110 people. The design of this research is a quantitative research of primary data by collecting data with a questionnaire. The results of the research revealed that work motivation, competence and work culture had a significant effect on the performance of the employees of the Directorate General of Agricultural Infrastructure and Facilities. Keywords: Work Motivation, Competence, Employee Performance. Directorate General of Agricultural Infrastructure and Facilities of RI.